Evaluation of Side Barriers to the Level of Service on the Kelok 9 Bridge Road Section - Arsyad, Nadra; Melasari, Jihan (CIVED, 2023)
The Kelok 9 Bridge is uniquely designed and supported by a beautiful natural panorama. On one of these 9 curves, a rest area has been provided for road traffic users to rest, or for urgent needs when driving on the road, but because of its strategic location and very beautiful shape, it is often used as a tourist destination by most people. who travel to or from West Sumatra. This raises a new problem, this is because the local community sells by building buildings on the shoulder of the 9th bend. So the purpose of this study is to determine the effect of side friction on the performance of the 9th road section based on the level of service. This research examined the data and then analyzed using the Indonesian Road Capacity Guidelines. So on Sunday from 16.00-17.00 the h, the highest traffic volume value is obtained, with a traffic volume of 2.2221 Skr/hour and has area of Saturation of 0.613, indicating that the traffic conditions are heavy. Because the Degree of Saturation value is 0.613, the level of service for Jalan Kelok 9 C can be concluded that the flow is stable but the speed of vehicle movement is controlled.